Pengetahuan dan Sikap Lansia tentang Booster COVID-19 di Desa Sukajaya Wilayah Kerja Puskesmas Cikondang Kabupaten Cianjur - Lusinda Pebrian; Hery Prayitno; Oktarian Pratama (Sehat MasadaJurnal, 2023)
Background: In 2020 the World Health Organization (WHO) announced that COVID-19 was categorized as a pandemic. COVID-19 continues to undergo mutations forming new variants. The new variant that has been detected is the Omicron variant. Vaccines are one way that can be done to break the chain of spread of COVID 19 is to vaccinate. In January 2022 Indonesia has started a third dose or booster vaccine program. This program is a form of continued efforts from primary vaccination. Objective: The purpose of this study was to determine the relationship between the level of knowledge and attitudes with the COVID-19 Booster Vaccination in the elderly in Sukajaya Village, Cikondang Health Center Working Area, Cianjur Regency. Methods: Analytical descriptive type of research through a cross-sectional approach. Results: The results of the research 36.7% had a good level of knowledge of the COVID-19 Booster vaccination, 57.8% had a positive attitude towards the COVID-19 Booster vaccination and there was a relationship between the level of knowledge and attitude with the COVID-19 booster vaccination with a p Value of 0.000. Conclusion: Elderly knowledge about the COVID-19 Booster vaccination in Sukajaya Village, Cikondang Health Center Work Area, Cianjur Regency in 2022 showed that 55 respondents (61.1%) were good. The attitude of the elderly regarding the COVID-19 Booster vaccination showed that 52 respondents (57.8%) were positive. There is a Relationship Between Knowledge and COVID-19 Booster Vaccination in Sukajaya Village, Cikondang Health Center Work Area, Cianjur Regency with p. Values 0.000.